2010
DOI: 10.1063/1.3529444
|View full text |Cite
|
Sign up to set email alerts
|

The impact of uncertainty on shape optimization of idealized bypass graft models in unsteady flow

Abstract: It is well known that the fluid mechanics of bypass grafts impacts biomechanical responses and is linked to intimal thickening and plaque deposition on the vessel wall. In spite of this, quantitative information about the fluid mechanics is not currently incorporated into surgical planning and bypass graft design. In this work, we use a derivative-free optimization technique for performing systematic design of bypass grafts. The optimization method is coupled to a three-dimensional pulsatile Navier-Stokes solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 53 publications
1
40
0
Order By: Relevance
“…The SMF has been used successfully in a variety of complex problems, including unsteady fluid mechanics [30][31][32], helicopter rotor blade design [33,34], quantifying uncertainity in bypass graft models [35] and identifying arterial G&R parameters [36]. The SMF method was originally developed for computationally expensive simulations and can be applied to discontinuous functions and problems with nonlinear constraints [37].…”
Section: Surrogate Management Framework (Smf)mentioning
confidence: 99%
“…The SMF has been used successfully in a variety of complex problems, including unsteady fluid mechanics [30][31][32], helicopter rotor blade design [33,34], quantifying uncertainity in bypass graft models [35] and identifying arterial G&R parameters [36]. The SMF method was originally developed for computationally expensive simulations and can be applied to discontinuous functions and problems with nonlinear constraints [37].…”
Section: Surrogate Management Framework (Smf)mentioning
confidence: 99%
“…This problem is studied in [3], which uses the stochastic collocation technique to incorporate and study the effects of input uncertainties, and applies a derivative-free optimization method to perform robust shape design.…”
Section: Problem Formulationmentioning
confidence: 99%
“…This method has the ability to converge to a mesh local optima for Lipschitz continuous functions. [3] demonstrated that accounting for implementation and measurement uncertainties affects the optimal graft attachment angle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, whenever some parameters are uncertain, we aim at inferring their values (and/or distributions) from indirect observations (and/or measures) by solving an inverse problem: given an observed output, can we deduce the value of the parameters that resulted in this output? Such problems are often encountered in cardiovascular mathematics as problems of parameter identification [7,70], variational data assimilation [13,50,63,66], or shape optimization [1,44,51,64]. Computational inverse problems are characterized by two main difficulties:…”
Section: Introductionmentioning
confidence: 99%